2018
DOI: 10.1111/jgs.15416
|View full text |Cite
|
Sign up to set email alerts
|

Community Pharmacists' Contribution to Medication Reviews for Older Adults: A Systematic Review

Abstract: Regardless of community pharmacists' contributions to interventions, medication review interventions seem to reduce drug-related problems and increase medication adherence. More well-designed, rigorous studies with more sensitive and specific outcomes measures need to be conducted to assess the effect of community pharmacists' contributions to reviewing medications and improving the health of older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 28 publications
1
62
0
1
Order By: Relevance
“…However, there is also evidence of significant variation in the range of activities already undertaken by pharmacists in carrying out this work, from simply providing a record of medications dispensed, to more collaborative interventions that directly engage with and support older people and practitioners with complex medication management. 151 Community pharmacists could be more involved in medication review interventions for older adults, with their contribution extending from identification of DRPs (drug related problems) to a more holistic contribution to medication therapy management. Kallio et al 151 Interventions involving pharmacists in medicines management, such as medicines reviews (with positive effects on adherence and use, medicines problems and clinical outcomes) and pharmaceutical care services (consultation between pharmacist and patient to resolve medicines problems, develop a care plan and provide follow-up; with positive effects on adherence and knowledge).…”
Section: Practitioner Experience and Expertisementioning
confidence: 99%
See 1 more Smart Citation
“…However, there is also evidence of significant variation in the range of activities already undertaken by pharmacists in carrying out this work, from simply providing a record of medications dispensed, to more collaborative interventions that directly engage with and support older people and practitioners with complex medication management. 151 Community pharmacists could be more involved in medication review interventions for older adults, with their contribution extending from identification of DRPs (drug related problems) to a more holistic contribution to medication therapy management. Kallio et al 151 Interventions involving pharmacists in medicines management, such as medicines reviews (with positive effects on adherence and use, medicines problems and clinical outcomes) and pharmaceutical care services (consultation between pharmacist and patient to resolve medicines problems, develop a care plan and provide follow-up; with positive effects on adherence and knowledge).…”
Section: Practitioner Experience and Expertisementioning
confidence: 99%
“…151 Community pharmacists could be more involved in medication review interventions for older adults, with their contribution extending from identification of DRPs (drug related problems) to a more holistic contribution to medication therapy management. Kallio et al 151 Interventions involving pharmacists in medicines management, such as medicines reviews (with positive effects on adherence and use, medicines problems and clinical outcomes) and pharmaceutical care services (consultation between pharmacist and patient to resolve medicines problems, develop a care plan and provide follow-up; with positive effects on adherence and knowledge). Ryan et al 111 Important role of pharmacists in taking accurate medication history across various hospital transitions.…”
Section: Practitioner Experience and Expertisementioning
confidence: 99%
“…Even though community pharmacists contribute to medication risk management in many ways, little is known regarding what risk management actions they actually take as part of routine dispensing [12][13][14]. Our recent systematic review indicated that medication review interventions involving community pharmacists could reduce medication-related risks and increase adherence in older adults [15]. The same systematic review also concluded that community pharmacists could contribute more to patient care than is currently the case, and more evidence should be available on the impact of the interventions of community pharmacists on medication risk management.…”
Section: Introductionmentioning
confidence: 99%
“…Community pharmacists have been shown to support medication reconciliation and adherence, which can improve chronic disease management. [20][21][22][23][24] Retinal screening in people with diabetes can be done using remote technology at an optometrist's office, with data being analysed off-site by trained ophthalmologists. 25 Technology, including wearable devices like portable oxygen saturation monitors and home blood pressure monitors that connect to electronic medical records, may also partially fill in portions of the clinical exam.…”
Section: Challenges To Making Virtual Care the Central Solutionmentioning
confidence: 99%